COVID-19 and retinal degenerative diseases: Promising link "Kaempferol". (June 2022) - Firoz, Arman; Talwar, Priti
Abstract: Coronavirus disease (COVID-19) outbreak has caused unprecedented global disruption since 2020. Approximately 238 million people are affected worldwide where the elderly succumb to mortality. Post-COVID syndrome and its side effects have popped up with several health hazards, such as macular degeneration and vision loss. It thus necessitates better medical care and management of our dietary practices. Natural flavonoids have been included in traditional medicine and have also been used safely against COVID-19 and several other diseases. Kaempferol is an essential flavonoid that has been demonstrated to influence several vital cellular signaling pathways involved in apoptosis, angiogenesis, inflammation, and autophagy. In this review, we emphasize the plausible regulatory effects of Kaempferol on hallmarks of COVID-19 and macular degeneration.